Exploring battery-type ZnO/ZnFe2O4 spheres-3D graphene electrodes for supercapacitor applications: advantage of yolk-shell over solid structures - Jhajharia, Suman Kumari; Manappadan, Zinoy; Selvaraj, Kaliaperumal (ChemElectroChem, 2019)
Recently, a ZnO/ZnFe2O4 composite has been reported to be a promising material for energy storage, owing to its large specific capacity and good redox activity. However, due to the inability to accommodate its strong volumetric variations during operation, it fails to retain its capacitance, which remains as a significant hitch. Herein, we present our attempt towards solving this through a binder-free electrode design comprising a porous yolk-shell ZnO/ZnFe2O4 composite matrixed inside a 3D network of graphene, which, in turn, is grown on Ni foam. The design exhibits a four-fold increase in its specific capacitance, yielding 1334 F g(-1) (specific capacity of 370.5 mAh g(-1)) at a current density of 0.5 A g(-1) in comparison to that of the ZnO/ZnFe2O4 electrodes (309 F g(-1) (85.8 mAh g(-1)) at 0.5 A g(-1)) comprising solid metal oxide spheres. The major advantage of the design is the well-defined yolk-shell architecture that provides free space for volume expansion during long cycling processes and channels for ionic transportation; whereas, the conductive 3D graphene network and porous Ni foam facilitate electronic conduction. The availability of free space in yolk-shell sphere electrodes facilitates the capacitance retention of up to 80 % beyond 5000 cycles at a current density of 1 A g(-1), which is in contrast to the capacitance retained by the solid spheres of only approximately 60 %. These results directly demonstrate the significant consequence of the yolk-shell architecture-based binder-free design and its promising potential in high-performing supercapacitors and batteries.
Keywords: binder-free electrodes; graphene hydrogels; Supercapacitors; volume expansion; yolk-shell spheres

Unravelling the distinct surface interactions of modified graphene nanostructures with methylene blue dye through experimental and computational approaches - Manappadan, Zinoy; Kumar, Shubham; Joshi, Krati; Govindaraja, Thillai; Krishnamurty, Sailaja; Selvaraj, Kaliaperumal (Journal of Hazardous Materials, 2020)
Nanoscopic modifications leading to multi-dimensional graphene structures are known to significantly influence their candidature for several applications including catalysis, energy storage, molecular sensing and most significantly adsorption and remediation of harmful materials such as dyes. The present work attempts to identify the key trajectories that connect the structural qualification with a chosen application, viz., the interactive forces in dye remediation. Various physico-chemically Modified Graphene Nanostructures (MGNs) such as 2 dimensional Graphite, Graphene Oxide (GO), reduced GO (rGO), holey rGO, and 3 dimensional GO hydrogel and Holey GO hydrogel are chosen and synthesised herein. These represent varieties of physicochemical features with respect to their dimensionality, surface features such as oxygen functionality, nanoscopic holes etc., that contribute to their characteristic overall surface interactions. Methylene Blue (MB), a popular industrial effluent posing major environmental concern is chosen to be a probe adsorbate in this case study. An exclusive real time in-situ UV visible spectral experiment provides the revealing reasons behind the outstanding performance of 2D GO sheets with an adsorption capacity of greater than 92 % even at high MB concentrations (>2000 ppm). A complex dependency of various factors such as surface oxygen, morphology, nanoporosity etc. on the unique overall interaction with an adsorbent such as MB by all these adsorbates is demonstrated using experimental and DFT based computational studies. Electrostatics and hydrogen bonding are understood to be the two dominant forces driving the MB adsorption on the best performing GO here.
Keywords: Density functional theory; In-situ UV-vis spectroscopy; Interactions; Methylene blue; Modified Graphene Nanostructures

Electrochemically tuned synergistic nano-interface of a tertiary Ni(OH)(2)-NiO(OH)/NixP heterojunction material for enhanced and durable alkaline water splitting - Manappadan, Zinoy; Selvaraj, Kaliaperumal (ChemistrySelect, 2022)
Making water splitting cheaper is the need of the hour.The present work reports a nickel-based, non-precious catalytic system, synthesized by a two-step electrodeposition (ED) process followed by a short-term heat treatment. The Ni(OH)(2)-NiO(OH)/NixP heterojunction has been synthesized and optimized through an unprecedented, energy-conserving method to achieve its best OER performance. Further, it has been carefully tuned for the first time by thoroughly optimizing the ED parameters to exhibit Hydrogen Evolution Reaction (HER). At high current regimes, the performance surpassed that of the Ru/C and Pt/C (>= 500 mA and >= 600 mA) respectively. The full cell electrolyzer configuring NOPO||NOPH further establishes the supremacy of the present electrocatalysts over the benchmark Ru/C||Pt/C. Moreover, the present electrocatalyst displayed 60 and 70 hours of HER and OER performances at -100 mA and 100 mA currents respectively. In short, this work is an example that illustrates how a single chemical system gets to exhibit two complementary catalytic behaviors that is, water oxidation and reduction when certain synthetic parameters are meticulously optimized.
Keywords: Electrodeposition; heterojunction; Ni(OH)(2)-NiO(OH); NixP; non-precious metal; water splitting